Revealing the Complexity in CD8 T Cell Responses to Infection in Inbred C57B/6 versus Outbred Swiss Mice - Martin, Matthew D.; Danahy, Derek B.; Hartwig, Stacey M.; Harty, John T.; Badovinac, Vladimir P. (Frontiers in Immunology, 2017)
Recent work has suggested that current mouse models may underrepresent the complexity of human immune responses. While most mouse immunology studies utilize inbred mouse strains, it is unclear if conclusions drawn from inbred mice can be extended to all mouse strains or generalized to humans. We recently described a ‘surrogate activation marker’ approach that could be used to track polyclonal CD8 T-cell responses in inbred and outbred mice and noted substantial discord in the magnitude and kinetics of CD8 T-cell responses in individual outbred mice following infection. However, how the memory CD8 T-cell response develops following infection and the correlates of memory CD8 T cell-mediated protection against re-infection in outbred mice remains unknown. In this study we investigated development of pathogen-specific memory CD8 T-cell responses in inbred C57B/6 and outbred NIH Swiss mice following LCMV or L. monocytogenes infection. Interestingly, the size of the memory CD8 T-cell pool generated and rate of phenotypic progression was considerably more variable in individual outbred compared to inbred mice. Importantly, while prior infection provided both inbred and outbred cohorts of mice with protection against re-infection that was dependent on the dose of primary infection, levels of memory CD8 T-cells generated and degree of protection against re-infection did not correlate with primary infection dose in all outbred mice. While variation in CD8 T cell responses to infection is not entirely surprising due to the genetic diversity present, analysis of infection-induced immunity in outbred hosts may reveal hidden complexity in CD8 T-cell responses in genetically diverse populations and might help us further bridge the gap between mouse and human studies.